Characteristics of Arabic Diminutive - Muftić, Teufik (Prilozi za orijentalnu filologiju, 2017)
The most common way of diminutive formation in the Arabic literary language (diminution, taṣġīr or taḥġīr) with basic forms: ju'ail, fu'ai'il and fu'ai'il, derived from various non-reduced forms, has been described in detail in Arabic normative grammar since the time of its first systematist Sībawaih. That is why this study provides only the most important information about this form. The second, much rarer way of diminution of those same basic forms, but done through derivation from the very root to which the concrete forms of the words from which one wants to obtain a diminutive are reduced, has been pointed out here in comparison with the first form. This has been done for two reasons. First, because of the existence of these two forms there appears, on the one hand, the formation of double diminutive forms of the same non-reduced word [e. g., from 'uṣfūr can be formed: l) 'uṣaifir or 2) 'uṣaifīr; from ḥamrā': 1) ḥumairā' or 2) ḥumairat, etc.]. On the other hand, in the second way of diminution in the word having the same root, diminut!ive forms cannot be differentiated (e. g. of the woro with the root f-r-s: fāris and faras the common diminutive form reads: furais, whereas in the first way the diminutives of these words are mutually clearly distinguishable and read: fuwairis or furais). Due to this possibility of distinguishing the forms of diminutives of words derived from the same root, the first manner has probably prevailed over the second in the living language practice. There exist a certain number of irregularly formed diminutives but they, in the filnal analysis, amount to the above mentioned basic forms and thus represent only a peculiarity in the morphological respect. In addition to the way of diminution by internal inflection already mentioned, there exist some other forms ordinarily used in the other meanings, whereas in the diminutive (and similar) sense they come only individually. Some of them come about by internal change of vocalism, and they are: l) fu'āl(at), as for example in ġulām or qurābat and 2) fulāfil(at) e. g. in: (ḥubḥāib or duwābbat (< duwābibat) and the like. Other diminutives come about by the addition of the suffix -ān to the non-reduced word (e. g. in 'aqrabān). This suffix, especially in the Maghreb countries, alternates in proper personal names with the suffix -ūn (e. g. in 'Abdān and 'Abdūn, and the like). The third group of forms of diminutive or deteriorative meaning appears by reduplication of the third radical of the trilateral (e. g. in duḫlūl, ğirbīb, qirṭīṭā, šaġṭūṭā, qamnānat, and the like). It is already a known fact that the Arabic diminutive is predominantly derived from nominal forms, most of all from nouns and adjectives (also participles), in some cases from some pronouns, prepositions (of nominal origin) and from some verbs. Although the diminutive in Arabic also has a semantic function of physical diminution (taṣġīr), it frequently evolves in this respect into other meanings acquiring a certain affective nuance either in the positive (hypocorism) or in the negative sense of contempt and the like (taḥqīr), whereas in some cases it can bring about the completely opposite values of certain abstract augmentation (taẓīm). However, surprising this last might seem at first sight, it can be explained on the one hand by the innate human way of thinking in contrasts and on the other, at least in a number of specifics cases by primitive mythological beliefs according to which something big and unpleasant can lose some of its fatal effect if it is designated by a word of diminutive form. Thus, it is believed that, by the magical power of the word itself, it is possible to remove such unfav10rable influence of the being, object or phenomenon designated by the diminutive. In addition to this basic function of diminution and meanings semantically connected with it, which a1so includes derivation of proper names, especially names of persons (formed from original hypocorisms ;but a1so frequently from opposite values), there exist a large number of diminutives which have, as it were, lost their original meaning and are thus used in the language practice just like any other non-reduced word without a sense of their etymology, although formally they bear a clear imprint of the diminutive. On account of this loss of their original value, and in order to establish it again, it is necessary to resort to other linguistic means of diminution outside the field of morphology - that of syntax or stylistics. However, such means go beyond the scope of thi1s paper and consequently have not been considered. The paper is confined to corresponding morphemes and their semantics and does not enter into the consideration of more complex linguistic forms connected with the problem of the diminutive in the Arabic literary language.